A STUDY OF NURSING ADMINISTATOR LEADERSHIP AMONG MULTIGENERATION PROFESSIONAL NURSES, PRIVATE HOSPITAL: ภาวะผู้นำ, หลากหลายรุ่นอายุ, โรงพยาบาลเอกชน - Wichitkultana, Sirinthip; Prachusilpa, Gunyadar (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2018)
The purpose of this qualitative research was to study leadership of nursing administrator among multigenerational professional nurses, in a private hospital. The subjects were expert group of 21 nursing administrators, human resources planner, and professional working in organization, private hospitals, academic institutions and instructor who teach in nursing administration. The Delphi technique consisted of 3 steps. Step 1, The experts were interviewed about the leadership of administrator among multigenerational in the workplace. Step 2, Using the content analysis of the initial data to develop the questionnaire and rating scales. Step 3, This data was analyzed by using median and interquartile range to develop a new version of the questionnaire. The new questionnaire was sent to same experts to confirm that the content of the new questionnaire was viable. Changes were made, so the questionnaire was analyzed again by median and interquartile range. The final questionnaire was administered and the results summarized. The results had 2 components as follows: 1.The characteristics of leadership. And this consists of three component; Personality characteristics, Emotional Intellectual and ethical. 2.The behavior of leader consists of two components: Team building and motivation.